Integrasi Islam dan Adat Minangkabau: Implementasi nilai agama dan tradisi adat dalam lingkungan masyarakat - Husna, Lativa; Hasaniyah, Nur (Maliki Interdisciplinary Journal, 2026)
This research aims to analyze the process of Islamization in Minangkabau and the integration of Islamic values with Minangkabau customs. Through a literature review, the study reveals that Islam entered Minangkabau via trade routes and underwent a long process of acculturation with local traditions. The concept of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK) serves as a fundamental pillar in regulating the relationship between religion and customs. Values such as consensus, mutual cooperation, and moral integrity are distinctive traits of the Minangkabau community, shaped by this blend. The research also examines the inheritance system in Minangkabau as a concrete example of the application of ABS-SBK. The findings indicate that Islam has become an integral part of Minangkabau identity, and the ABS-SBK concept has successfully fostered harmony between religion and culture.